Physical, mechanical and thermal properties of oil palm cellulose nanofiber filled natural fiber reinforced polylactic acid hybrid composites for sustainable furniture - Azka, Muhammad Adlan; Mousa, Saaed Abdullah; Siddiqui, Vasi Uddin; Sapuan, S. M.; Rahman, M. A.A.; Murphy, Adrian; Abral, Hairul; Mahardika, Melbi; Hidzer, M. Hazim; Hafiraj, Zahran (Taylor and Francis, 2026)
Wood polymer composites (WPC) face environmental challenges in waste disposal, wood overexploitation, and wood utilization stricter regulations. Therefore, this study explores using natural fibers like bamboo and kenaf as substitutes for wood, combined with biopolymers such as polylactic acid (PLA). However, previous findings indicate that the properties of these composites are lower than conventional materials. Therefore, the objective of this research is to enhance the physical, mechanical, and thermal properties of polylactic acid composites with fixed bamboo and kenaf fiber loading by varying oil palm cellulose nanofiber for improved furniture applications. The results showed an improvement in mechanical properties, such as the tensile strength of 40.28 MPa, a tensile modulus of 2858.36 MPa, and an elongation at break of 2.27% and lighter-weight composites (5.09% density reduction) with the addition of OPCNF. Besides, the T20 and T50 values remained very close for all the samples, which confirms that the incorporation of OPCNF did not reduce the thermal stability. Further, the values of Tg and Tcc improved to 62.14°C and 110.74°C, respectively. This study may allow the furniture industry to create a more sustainable product with good characteristics to replace harmful chemicals, allowing it to be applied to more uses in furniture.